Answer: f(3) = 14
Concept:
Here, we need to understand the idea of evaluation.
When encountering questions that gave you an expression with variables, then stated: "If x = a, y = b, z = c" (a, b, c are all constants), this means you should substitute the value given for each variable back to the expression.
Solve:
Given function
f(x) = 4x + 2
Substitute value of the x into the expression
f(3) = 4(3) + 2
Simplify by multiplication
f(3) = 12 + 2
Simplify by addition
f(3) =
Hope this helps!! :)
Please let me know if you have any questions